A note on the Chisholm parameter equation in RELAP. (March 2020) - Awad, M.M.
Highlights: A note on the C value in RELAP is presented. C equation used in RELAP gives unphysical values in the high mass flux condition. The C value in RELAP cannot be negative. Abstract: In this study, A note on the Chisholm parameter (C) equation in RELAP is presented. In literature, some researchers mentioned that the Chisholm parameter (C) value in RELAP could be calculated from the modified Baroczy correlation in terms of total mass flux (G), and the properties of each phases (ρg, μg, ρf, μf ). From this note, it can be shown that the Chisholm parameter (C) is less than zero at high values of the mass flux (G) for the Baroczy dimensionless property index (Λ) value = 0.0019. This is incorrect because the minimum value of the Chisholm parameter (C) is zero.